7a, 25-dihydroxycholesterol-mediated activation of EBI2 in immune regulation and diseases - Sun, Siquan; Liu, Changlu (Frontiers in Pharmacology, 2015)
EBI2, aka GPR183, is a G-couple receptor originally identified in 1993 as one of main genes induced in Burkitt’s lymphoma cell line BL41 by Epstein-Barr virus (EBV) infection. After it was reported in 2009 that the receptor played a key role in regulating B cell migration and responses, we initiated an effort in looking for its endogenous ligand. In 2011 we and another group reported the identification of 7a, 25-dihydroxyxcholesterol (7a, 25-OHC), an oxysterol, as the likely physiological ligand of EBI2. A few subsequently published studies further elucidated how 7a, 25-OHC bound to EBI2, and how a gradient of 7a, 25-OHC could be generated in vivo and regulated migration, activation, and functions of B cells, T cells, dendritic cells (DC), monocytes/macrophages and astrocytes. The identification of 7a, 25-OHC as a GPCR ligand revealed a previously unknown signaling system of oxysterols, a class of molecules which exert profound biological functions. Dysregulation of the synthesis or functions of these molecules is believed to contribute to inflammation and autoimmune diseases, cardiovascular diseases, neurodegenerative diseases, cancer as well as metabolic diseases such as diabetes, obesity, and dyslipidemia. Therefore EBI2 may represent a promising target for therapeutic interventions for human diseases.